EFEKTIVITAS IMPLEMENTASI PENJAMINAN MUTU PENDIDIKAN TERHADAP KINERJA SD NEGERI KENAWA KABUPATEN LOMBOK TENGAH - Aldi Nurrasyid; Dwi Lestari, Riza; Lilik Yulia Astuti, Baiq; Faizah Habibatul Husna; Redan Werang, Basilius (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Educational quality is a key indicator of school performance and the success of educational management. The implementation of the Internal Quality Assurance System (SPMI) is expected to support continuous school improvement through systematic quality management. This study aimed to analyze the effectiveness of educational quality assurance policy implementation in improving school performance at SD Negeri Kenawa, Central Lombok Regency. A qualitative approach with a case study design was employed. Data were collected through observations, semi-structured interviews, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The analysis was guided by George C. Edward III’s policy implementation model, which includes communication, resources, disposition, and bureaucratic structure. The findings indicate that the quality assurance policy has been implemented through the establishment of the School Quality Assurance Team (TPMPS), the application of the PPEPP cycle, Data-Based Planning (PBD), academic supervision, and continuous teacher professional development. These efforts contributed to improved literacy and numeracy outcomes. However, school diversity climate, school safety climate, and instructional quality remain areas requiring improvement. The study concludes that the implementation of the quality assurance policy is generally effective but requires continuous strengthening of quality culture, optimization of the PPEPP cycle, and improvement of educational facilities to achieve sustainable school quality enhancement.